Kurikulum untuk Pengembangan Modul Pembelajaran Peningkatan Bobot Kambing di Era New Normal - K. Anom W; Yesi Hikmahtika; Eka Ad'hiya; Abdurachman Ibrahim (Chemistry Education Department of Education and Teaching Faculty, 2023)
The purpose of this study was to analyze the curriculum for entrepreneurship courses as a learning module development for the Science Technology Engineering Mathematics approach in the New Normal era, feed for increasing the weight of goats in the growth phase. The respondents of this study were students in semester 5 of the 2021/2022 academic year of Chemistry Education, Faculty of Teacher Training and Education, Sriwijaya University. This research method is descriptive, researchers analyze data from interviews with chemistry education students in semester 5 of the 2021/2022 academic year and documentation. The results of the questionnaire on 6th semester chemistry education students who strongly agreed were 61.90% for item 1) The learning module for entrepreneurship courses contained material about raising goats to increase the weight of goats. A total of 47.61% of students strongly agree with point 2) The revised curriculum is revised in order to foster entrepreneurial attitudes and motivation. A total of 38.09% stated strongly agree to item 3) Entrepreneurship curriculum characterized by chemistry (chemo-entrepreneurship). as much as 52.38% strongly agree with item 4) The entrepreneurship curriculum uses the STEM approach. a total of 52.38% strongly agree with point 5) In the New Normal era the curriculum must be carried out with entrepreneurs. The conclusion of the study is that the entrepreneurship curriculum needs to be revised so that students can adapt in the New Normal era so that a learning module with the topic of feed types is needed to increase goat weight.